2020
DOI: 10.1002/fsn3.1435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vacuum cooling on stability of macro‐porous sausage during refrigerated storage—Vacuum‐cooled sausage has a longer shelf life

Abstract: In this study, two types of cooling methods (vacuum cooling and air cooling) were used to cool cooked macro‐porous sausage. Alterations in the microbiological conditions, pH, instrumental color (L*, a*, and b*), total volatile nitrogenous bases (TVB‐N), lipid oxidation (TBARS), water activity (aW), moisture content, and texture indicators were evaluated to determine sausages' quality changes during storage under refrigeration for up to 10 days. In general, the shelf life of sausages chilled by vacuum cooling (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…The boiling point temperature of water can be reduced by increasing the vacuum in the drying chamber, so that the water in the object can evaporate at a lower temperature. However, a degraded in food quality (Liao and Yu, 2020;Song et al, 2020) and the restrictions on samples that could not be cooled is observed after VC which severely limits the promotion of vacuum cooling technology (Rodrigues et al, 2013). Therefore, it is crucial to identify solutions that can reduce the quality loss of food after vacuum cooling.…”
Section: Introductionmentioning
confidence: 99%
“…The boiling point temperature of water can be reduced by increasing the vacuum in the drying chamber, so that the water in the object can evaporate at a lower temperature. However, a degraded in food quality (Liao and Yu, 2020;Song et al, 2020) and the restrictions on samples that could not be cooled is observed after VC which severely limits the promotion of vacuum cooling technology (Rodrigues et al, 2013). Therefore, it is crucial to identify solutions that can reduce the quality loss of food after vacuum cooling.…”
Section: Introductionmentioning
confidence: 99%